Item‐level analysis of clinical measures in patients with early symptomatic Alzheimer's disease following treatment with high‐dose aducanumab in the phase 3 study EMERGE. (31st December 2021) - Cohen, Sharon; He, Ping; Benea, Mihaela Levitchi; Miller, Ryan; Forrestal, Fiona; Pang, Menglan; Castrillo‐Viguera, Carmen; Harrison, John E; Jaeger, Judy; Mummery, Catherine J.; Porsteinsson, Anton P.; Cummings, Jeffrey L.; et al.
Abstract: Background: EMERGE (NCT02484547), 1 of 2 Phase 3 trials evaluating aducanumab in patients with early Alzheimer's disease (AD), demonstrated a statistically significant drug‐placebo difference in the prespecified primary and secondary clinical endpoints. We examined in EMERGE participants the change from baseline item‐level scores in primary, secondary, and tertiary clinical endpoints that, in combination, comprised a set of cognitive, functional, and neuropsychiatric instruments that provide a comprehensive assessment of AD. Method: EMERGE (N=1643) included participants aged 50‐85 years who met clinical criteria for MCI due to AD or mild AD dementia, with confirmed amyloid pathology. Participants were randomized to receive high‐dose aducanumab, low‐dose aducanumab, or placebo. The primary endpoint was change from baseline in CDR‐SB score at Week 78. Secondary outcome measures included MMSE, ADAS‐Cog13, and ADCS‐ADL‐MCI scores. NPI‐10 score was a tertiary outcome. Item‐level analyses using mixed model for repeated measures (MMRM) were conducted on these clinical efficacy endpoints using the ITT population. This analysis is considered descriptive due to its deviation from the normality assumption and thus no multiplicity adjustment was considered. Result: The aducanumab high‐dose group demonstrated a consistent drug‐placebo difference across 5 clinical efficacy endpoints, slowing clinical decline over 78 weeks. Treatment effects were observed across all 6 domains of the CDR. An aducanumab treatment effect was evident by slowing of decline on the ADAS‐Cog13 items sensitive to change in early symptomatic AD (e.g., orientation, word recall [immediate and delayed], word recognition, and number cancellation). Additionally, clinical benefit of aducanumab with respect to preserving daily function was observed across a broad range of items on the ADCS‐ADL‐MCI. Finally, aducanumab treatment was associated with an attenuation of behavioral and psychiatric symptoms associated with AD, as measured by NPI‐10, and an accompanying decrease in caregiver distress. Conclusion: Aducanumab treatment effects, observed across a broad array of outcome measures, are clinically relevant. Item‐level analyses demonstrated consistency across cognitive, function, and behavioral domains sensitive to impairments that are detectable even in the early stages of AD. Holistically, these measures reflect the perspectives of patients, caregivers, and clinicians, thereby supporting the importance and meaningfulness of an aducanumab treatment effect in early AD.